2011
DOI: 10.1016/j.jcws.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium Tertium Isolated From a Necrotizing Soft Tissue Infection in a Diabetic but Otherwise Nonimmunocompromised Patient

Abstract: Clostridium tertium has historically been regarded as nonpathogenic, and its implication as the primary microbe in infectious etiologies remains unclear. Although there have been several reports of C tertium isolated from blood, tissue, and other specimens, largely this population has consisted of patients with neutropenia, hematologic malignancies, or gastrointestinal disorders. Here we describe a case of a 39-year-old nonimmunocompromised man with a history of type 1 diabetes mellitus and intravenous drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…CT MALS001 exhibited genomic and phenotypic susceptibility to both ciprofloxacin and vancomycin. This is concordant with the pathogenic profile of C. tertium which is largely considered as a non-pathogenic strain that is occasionally found in clinical cases (Moore and Lacey, 2019;Steensma et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…CT MALS001 exhibited genomic and phenotypic susceptibility to both ciprofloxacin and vancomycin. This is concordant with the pathogenic profile of C. tertium which is largely considered as a non-pathogenic strain that is occasionally found in clinical cases (Moore and Lacey, 2019;Steensma et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…The increased incidence of NSTIs in IVDA has been a world-wide phenomenon in recent years that is supported by several retrospective studies [39][40][41][42][43][44][45][46][47]. Methods of injecting drugs into the subcutaneous region otherwise known as "skin-popping" may explain this phenomenon.…”
Section: Discussionmentioning
confidence: 97%
“…Although C. tertium has traditionally been considered non-pathogenic, various studies have reported it to be a significant cause of bacteremia and other infections in neutropenia patients [ 29 , 49 , 50 , 53 , 60 ]. In addition, C. tertium infections in non-neutropenic patients have also been reported recently [ 57 , 58 , 62 ]. Odoribacter splanchnicus ( Bacteroides splanchnicus ) is an anaerobic gram-negative bacterium in Bacteroidetes .…”
Section: Discussionmentioning
confidence: 99%